2016
DOI: 10.1097/htr.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Catechol-O-methyltransferase on Executive Functioning Longitudinally After Early Childhood Traumatic Brain Injury

Abstract: Objective To elucidate the association of a functional catechol-O-methyltransferase (COMT) genotype (rs4680) with recovery of executive functions up to 18 months after early childhood traumatic brain injury (TBI) compared to an orthopedic injury (OI) group. Setting Outpatient Participants 134 children with a moderate to severe TBI (n=63) or OI (n=71) between the ages of 3-6 years who were followed 18 months post-injury Design Case-comparison, longitudinal cohort Main Measures The Behavior Rating Invent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Prior work in adult and pediatric TBI indicates the COMT rs4680 genotypes may be associated with recovery of cognitive and behavioral functioning after injury; 28,59,62 however, this prior work has not considered environmental factors also related to recovery. Similar to this prior work, results from the current study indicate that the low activity rs4680 COMT genotype (AA) is associated with improved executive functioning after traumatic injuries (i.e., TBI and OI), especially in the context of an authoritarian parenting behavior environment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior work in adult and pediatric TBI indicates the COMT rs4680 genotypes may be associated with recovery of cognitive and behavioral functioning after injury; 28,59,62 however, this prior work has not considered environmental factors also related to recovery. Similar to this prior work, results from the current study indicate that the low activity rs4680 COMT genotype (AA) is associated with improved executive functioning after traumatic injuries (i.e., TBI and OI), especially in the context of an authoritarian parenting behavior environment.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies suggest that variations in the COMT rs4680 genotype are related to outcomes after adult and pediatric TBI. 5962 Recent work with the same cohort studied in this study has demonstrated an association of the COMT rs4680 genotype with executive function outcomes up to 18 months after moderate to severe TBI and orthopedic injury (OI) in children age 3–7 years at the time of injury. 62 …”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations